Answer:
y = 9
Step-by-step explanation:
Given
4 +
= 7
Isolate the term in y by subtracting 4 from both sides
= 3 ( multiply both sides by 3 )
y = 3 × 3 = 9
Answer: 2 (x+5)
Step-by-step explanation:
Answer: the exponent would be the 2
Step-by-step explanation:
You can do this by comparing your equation to the general form of equation of a circle
( x - a)^2 + (y - b)^2 = r^2 where (a,b) is the centre and r = radius:-
(x + 9)^2 (y + 6)^2 = 9
so (a,b) = (-9,-6) and r = 3
so the answer is B
-8 - 7x is the factored version.